MAKNA LAFADZ TARBIYAH DENGAN TERM LAIN YANG IDENTIK DALAM AL QURAN - Lailatul Mas'udah (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2018)
Abstract: This research article discusses the meaning of Trabiyah with a number of other pronunciations related to it. Because in the Qur'an, there are several terms related to education, including Ta'lim and Tarbiyah. This writing uses the library research method by finding and comparing lafad related to Tarbiyah. By examining a number of interpretations and Arabic dictionaries, the authors sought to examine from each lafad identical to the word Tarbiyah. There are several terms that are identical with the meaning of education including; Ta'lim, Tadris, Ta'dib and Tazkiyah. Some of these words not only differ in meaning and their use and context, but also affect the process of an education. Every human being will go through the stages of education that are passed, and each stage that is passed there is a connection in the terms above, so it is very clear and can be ascertained, every lafad in the Koran does not exist which is a synonym form, but carries meaning and their respective roles.Keyword: Education, Tarbiyah